Description of Student Errors in Solving the Volume Of Cube and Beam For Class IX SMP Negeri 2 Mattiro Bulu, Pinrang Regency - Anugrah, Dian; Nurdin, Nurdin; Sumi, Sumi (Sublim: Jurnal Pendidikan, 2023)
This research includes qualitative research. This study aims to find out how to analyze the types of errors and the factors that cause errors in class IX.1 students of SMP Negeri 2 Mattiro Bulu, Pinrang Regency on the volume of cubes and blocks. This type of error analysis assessment consists of a test sheet and an interview guide sheet. The analysis of the types of errors produced in the study is indicated to be able to meet the indicators of the types of errors. The trial respondents in this study were students of class IX.1 of SMP Negeri 2 Mattiro Bulu, Pinrang Regency, as many as 24 students. Analysis of the types of errors in this study uses 3 (three) types of errors, namely: (1) reading error, (2) transformation error, and (3) encoding error . The factors that cause student errors in solving the volume problems of cubes and blocks are: (1) less thorough in answering questions, (2) forgetting formulas, and (3) making mistakes in operating.